Cardiovascular effects of a continuous rate infusion of lidocaine in calves anesthetized with xylazine, midazolam, ketamine and isoflurane - Araujo, Marcelo A.; Dias, Bianca P. [UNESP]; Bovino, Fernanda [UNESP]; Deschk, Mauricio [UNESP]; Abimussi, Caio J. X. [UNESP]; Oliva, Valeria N. L. S. [UNESP]; Rodrigues, Celso A. [UNESP]; Santos, Paulo S. P. [UNESP] (Wiley-Blackwell, 2014)
Objective To assess the cardiovascular changes of a continuous rate infusion of lidocaine in calves anesthetized with xylazine, midazolam, ketamine and isoflurane during mechanical ventilation.Study designProspective, randomized, cross-over, experimental trial.AnimalsA total of eight, healthy, male Holstein calves, aged 10 +/- 1months and weighing 114 +/- 11kg were included in the study.MethodsCalves were administered xylazine followed by ketamine and midazolam, orotracheal intubation and maintenance on isoflurane (1.3%) using mechanical ventilation. Forty minutes after induction, lidocaine (2mgkg(-1) bolus) or an equivalent volume of saline (0.9%) was administered IV followed by a continuous rate infusion (100 mu gkg(-1)minute(-1)) of lidocaine (treatment L) or saline (treatment C). Heart rate (HR), systolic, diastolic and mean arterial pressures (SAP, DAP and MAP), central venous pressure (CVP), mean pulmonary arterial pressure (mPAP), pulmonary arterial occlusion pressure (PAOP), cardiac output, end-tidal carbon dioxide (Pe ' CO2) and core temperature (CT) were recorded before lidocaine or saline administration (Baseline) and at 20-minute intervals (T20-T80). Plasma concentrations of lidocaine were measured in treatment L.ResultsThe HR was significantly lower in treatment L compared with treatment C. There was no difference between the treatments with regards to SAP, DAP, MAP and SVRI. CI was significantly lower at T60 in treatment L when compared with treatment C. PAOP and CVP increased significantly at all times compared with Baseline in treatment L. There was no significant difference between times within each treatment and between treatments with regards to other measured variables. Plasma concentrations of lidocaine ranged from 1.85 to 2.06 mu gmL(-1) during the CRI.Conclusion and clinical relevanceAt the studied rate, lidocaine causes a decrease in heart rate which is unlikely to be of clinical significance in healthy animals, but could be a concern in compromised animals.
Keywords: lidocaine; mechanical ventilation; hemodynamic; cattle